Site‐specific clinical disease onset in multiple sclerosis. (8th September 2014) - Willis, M. D.; Harding, K. E.; Wardle, M.; Pickersgill, T. P.; Tomassini, V.; Loveless, S.; Robertson, N. P.
<x xml:space="preserve">Abstract</x> Background and purpose Multiple sclerosis is a chronic inflammatory disorder of the central nervous system characterized by acute episodes of neurological dysfunction thought to reflect focal areas of demyelination occurring in clinically eloquent areas. These symptomatic relapses are generally considered to be random clinical events occurring without discernible pattern. The hypothesis that relapses may follow a predetermined sequence and may provide insights into underlying pathological processes was investigated. Methods Employing prospective clinical database data from 1482 patients who had experienced one or more consecutive relapses were analysed. Using regression analysis, site and symptom of index event were compared with those of first relapse. Results It is demonstrated that following disease ignition subsequent relapses may not be random events but dependent on characteristics of the index event. All anatomical sites were more likely to be affected in the first relapse if that site had been involved in the index event with a similar association observed when comparing by symptoms. Conclusion These findings have importance in understanding the evolution of the disease and predicting individual disease progression and may aid with patient counselling and management.